Optimalisasi peran orang tua dalam pendidikan seksual anak melalui seminar parenting di MI Syihabuddin Malang - Mubarokah, Siti; Najya, Shoffany Mafaza (Maliki Interdisciplinary Journal, 2025)
Early childhood sexual education is an important part of character building and protecting children from the risk of violence and behavioral deviations. However, many parents still feel awkward, lack information, or have a wrong understanding of sexual education. For this reason, We, the AM-MI Syihabuddin Group, collaborated with schools to initiate parenting seminar activities that aim to improve parents’ understanding and skills in providing sexual education that is appropriate to the child’s developmental stage. This study aims to describe the implementation of parenting seminars and their impact on parents’ knowledge and readiness in delivering sexual education to children. Using a qualitative approach, data were obtained through observation, interviews, and documentation. The results of the study showed that parenting seminars made a positive contribution to increasing parents’ sexual literacy, building open communication between parents and children, and strengthening cooperation between schools and families in assisting children’s overall development. These findings recommend the need for further education programs and more active involvement from various parties in supporting holistic and value-based sexual education for children.